Smart universities: Adaption challenges for Historically black universities in South Africa: A concept overview. - Dr. Victor H Mlambo; Dr. Hlanganani Mnguni (NUST Journal of Social Sciences and Humanities)
Universities today are experimenting with AI and big data to improve how students live and learn on campus; however, from a South African perspective, the question is: can historically black universities adapt to this ever-changing higher education environment? This paper employed a qualitative research method to answer these questions, and secondary data was sourced from engaging current literature. The paper found that infrastructure challenges, a lack of skills and development and limited resources were major factors hindering historically black universities from adopting the concept of a smart university; historically black universities offered minimal no techfocused courses, which reduced them to acclimatize themselves with the elements of the 4IR. The implications have been that historically black universities will struggle to catch up to previously white universities in transitioning their campuses from the traditional model of higher education to the concept of a smart campus.